Infectivity of Proviral DNA from Avian Sarcoma Virus-Transformed Mammalian Cells - Catala, Françoise (1979)
The number of Rous viral genomes in the cellular DNA from two subclones (RS2/3, RS2/6) derived from the same clone of hamster BHK-21 cells transformed by Rous sarcoma virus was determined by hybridization with viral complementary DNA made in vitro, and the capacity of the cellular DNA to infect (transfect) chicken embryo fibroblasts was compared before and after shearing this DNA to about the size of the provirus (6 × 10(6) to 7 × 10(6) daltons). The two subclones differed widely both in their capacity to give rise to virus (inducibility) after fusion with chicken embryo fibroblasts and in level of expression of viral proteins. It was shown that cells of both subclones contain a single copy of Rous DNA and yield infectious DNA. However, whereas transfection of chicken embryo fibroblasts was successful with both unsheared (≥18 × 10(6) daltons) and sheared DNA from the most inducible subclone (RS2/3 subclone), which also expresses viral proteins to an appreciable amount, transfection with DNA from the least inducible subclone (RS2/6 subclone), in which viral proteins are not expressed, succeeded only with sheared DNA. It was then about as successful as with sheared or unsheared RS2/3 DNA. The lack of infectivity of unsheared RS2/6 DNA may be explained by the hypothesis proposed by Cooper and Temin (G. M. Cooper and H. T. Temin, J. Virol. 17:422-430, 1976) to explain the lack of infectivity of DNA from certain chicken cells producing spontaneously low amounts of RAV-0 and resistant to exogenous RAV-0 infection, that is, that the viral genome (proviral DNA) is linked to a cis-acting control element which blocks its expression. This linkage might originate, in RS2/6 cells, from translocation of cellular DNA containing the single proviral copy.